Taking psychotherapy into sport—A clinical perspective. Issue 4 (24th September 2021) - Bloom, Gary
Abstract: Gary Bloom, the first psychotherapist to work in a professional football club, discusses how he has adapted his traditional psychotherapeutic training to match the demands of working with elite athletes, providing support for their performance improvement and more widely, their emotional and mental health.